2020
DOI: 10.1590/0034-7167-2018-0997
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress in nursing professionals of a university hospital

Abstract: Objectives:To identify the presence of occupational stress in nursing professionals of a university hospital in the inlands of the state of Minas Gerais and examine influence of sociodemographic and occupational characteristics in this disease. Methods: Cross-sectional, exploratory and quantitative study with 124 professional nurses from a university hospital in the inlands of the state of Minas Gerais. The adapted and validated Portuguese version of the Job Stress Scale (JSS) was used for the performance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
31

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 21 publications
2
16
0
31
Order By: Relevance
“…In this study, it was verified that the characteristics of the Nursing professionals are similar to those of other research studies in Brazilian hospital units ( 1 , 7 , 9 , 18 ) . These data were also observed in a study developed in a university hospital in the state of Minas Gerais, where 87.9% of the professionals were women, with a mean age of 40.2 years old ( 19 ) . Another study conducted with Nursing technicians in Montes Claros, Minas Gerais, indicated that 58.6% were female, with a mean age of 38.5 years old ( 20 ) .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In this study, it was verified that the characteristics of the Nursing professionals are similar to those of other research studies in Brazilian hospital units ( 1 , 7 , 9 , 18 ) . These data were also observed in a study developed in a university hospital in the state of Minas Gerais, where 87.9% of the professionals were women, with a mean age of 40.2 years old ( 19 ) . Another study conducted with Nursing technicians in Montes Claros, Minas Gerais, indicated that 58.6% were female, with a mean age of 38.5 years old ( 20 ) .…”
Section: Discussionsupporting
confidence: 60%
“…These differences in the sleep classification using the same research instruments are associated with lifestyle, workload, the physiological stress of each individual ( 28 ) , gender, age, presence of children, the personality of each professional and the economic conditions of the country ( 1 ) . In addition to that, the exposure to environmental factors and to work dynamics with high workload and stress is associated with the development of sleep changes ( 3 , 5 , 11 , 19 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Quanto ao curto prazo para cumprir ordens relacionadas ao trabalho, estudos sobre o estresse e distúrbios psíquicos nos trabalhadores de enfermagem foi encontrado que a velocidade para a realização das ações e o tempo geram pressões psicológicas e, portanto, predispondo o desencadeamento da SB (Santana et al, 2020).…”
Section: Discussionunclassified
“…Research, Society and Development, v. 10, n. 9, e35610918062, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i9.18062 o ritmo de trabalho acelerado, as dobras de plantão, existência de salários injustos incompatíveis com a realidade e a sobrecarga trabalhista pode afetar o desempenho físico, emocional e mental (Santana et al, 2020).…”
Section: Discussionunclassified
“…Quer seja pela exposição diária a riscos químicos, físicos, ergonômicos, de acidentes por material biológico ou pelos riscos psicossociais como sobrecarga, precariedade das condições de trabalho e pressões exercidas pelos superiores, pacientes e seus familiares/acompanhantes 10 . Estes fatores atingem os indivíduos e podem influenciar a atuação da equipe, gerando um quadro de insegurança para assistência à saúde 11 que, por vezes, favorece o adoecimento dos trabalhadores 12 .…”
Section: Introductionunclassified